FUNGSI PENGAWASAN DPRD DALAM PENETAPAN PERATURAN DAERAH APBD DI KANTOR DPRD SUMUT - Soetarto Soetarto; Elisabeth Sitepu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2020)
This study aims at examining and finding out the functions of the DPRD in the determination of the APBD Regional Regulation and determining answers and problem solving for obstacles in the DPRD supervision practice, and providing solutions to the functions of the DPRD in terms of overseeing the APBD Regional Regulation. This research uses a perspective method / qualitative approach. Data were collected from documents in the field and the results of interviews written and analyzed. The results of this study are that the DPRD has not been optimal in carrying out its supervisory function which involves the community by obtaining information from community leaders. Parliamentary oversight related to Law No. 32/2004 which states that the DPRD carries out oversight of the implementation of the local regulation because it is not the same condition as DPRD members who do not make recommendations for supervision of policies, projects or specific cases.